2008
DOI: 10.1016/j.cellsig.2007.10.030
|View full text |Cite
|
Sign up to set email alerts
|

xCT expression reduces the early cell cycle requirement for calcium signaling

Abstract: Calcium has long been recognized as an important regulator of cell cycle transitions although the mechanisms are largely unknown. A functional genomic screen has identified genes involved in the regulation of early cell cycle progression by calcium. These genes when overexpressed confer the ability to bypass the G1/S arrest induced by Ca 2+ -channel antagonists in mouse fibroblasts. Overexpression of the cystine-glutamate exchanger, xCT, had the greatest ability to evade calcium antagonist-induced cell cycle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 79 publications
1
15
0
Order By: Relevance
“…In addition, upregulation of xCT expression, cystine/cysteine uptake, and intracellular GSH levels have been associated with resistance to cancer therapy (Huang et al, 2005;Diaz et al, 2008). Indeed, the xCT-overexpressing HT1080 model cells used in these experiments are resistant to dihydropyridines and cobalt chloride (Lastro et al, 2008). Importantly, xCT expression is induced by both ATO and Dar, leading to cytoprotection against ATO, but leading to increased import for Dar.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, upregulation of xCT expression, cystine/cysteine uptake, and intracellular GSH levels have been associated with resistance to cancer therapy (Huang et al, 2005;Diaz et al, 2008). Indeed, the xCT-overexpressing HT1080 model cells used in these experiments are resistant to dihydropyridines and cobalt chloride (Lastro et al, 2008). Importantly, xCT expression is induced by both ATO and Dar, leading to cytoprotection against ATO, but leading to increased import for Dar.…”
Section: Discussionmentioning
confidence: 91%
“…To strengthen and expand our hypothesis beyond NB4 cells, we used several cell line models of non-APL malignancies. First, we used a previously characterized in vitro model of increased xCT activity, HT1080 human fibrosarcoma cells transduced with an empty retroviral vector or one directing the expression of xCT (Lastro et al, 2008). We compared and assessed apoptosis in the modified HT1080 cell lines following 48 hours of treatment with 2-5 mM Dar or DMAC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, thermal injury causes defects in T cell signaling involving problems in Ca 2+ mobilization. A recent study demonstrated that xCT expression in mouse fibroblasts could bypass the G1/S arrest induced by Ca 2+ -channel antagonists [48,49]. Also, a recent study demonstrated increased splenic xCT expression a murine model of endotoxemia and sepsis which is commonly associated with thermal injury [30].…”
Section: Discussionmentioning
confidence: 96%
“…Most recent work suggested that xCT can directly affect cell proliferation through regulation of AP-1 activity (Lastro et al, 2008). AP-1 transcriptional activity is increased when xCT is overexpressed.…”
Section: Discussionmentioning
confidence: 99%